2019
DOI: 10.1002/hep.30430
|View full text |Cite
|
Sign up to set email alerts
|

5‐Hydroxytryptamine Receptor 1D Aggravates Hepatocellular Carcinoma Progression Through FoxO6 in AKT‐Dependent and Independent Manners

Abstract: Serotonin and its receptors have been shown to play critical regulatory roles in cancer biology. Nevertheless, the contributions of 5‐hydroxytryptamine 1D (5‐HT1D), an indispensable member of the serotonergic system, to hepatocellular carcinoma (HCC) remain unknown. The present study demonstrated that the 5‐HT1D expression level was significantly up‐regulated in HCC tissues and cell lines. The 5‐HT1D expression level was closely correlated with unfavorable clinicopathological characteristics. Survival analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 45 publications
2
30
0
Order By: Relevance
“…Our studies show that the AKT signal activation is closely associated with the Tmod3 expression. On integrating the decrease in MMP proteins expression after Tmod3 knockdown and PIK3 enzyme activity assay, we conclude that Tmod3 influences MMP2, MM9 and MMP9 protein expression to promote of HCC cell metastasis by activating AKT signaling pathway, which has a crucial part in the HCC occurrence and development . Our data is also indicative of selective modulation by Tmod3 of EGFR‐PI3K‐AKT signaling in HCCs which, in turn, is modulated by EGF, without affecting HGF‐stimulated signaling.…”
Section: Discussionmentioning
confidence: 58%
“…Our studies show that the AKT signal activation is closely associated with the Tmod3 expression. On integrating the decrease in MMP proteins expression after Tmod3 knockdown and PIK3 enzyme activity assay, we conclude that Tmod3 influences MMP2, MM9 and MMP9 protein expression to promote of HCC cell metastasis by activating AKT signaling pathway, which has a crucial part in the HCC occurrence and development . Our data is also indicative of selective modulation by Tmod3 of EGFR‐PI3K‐AKT signaling in HCCs which, in turn, is modulated by EGF, without affecting HGF‐stimulated signaling.…”
Section: Discussionmentioning
confidence: 58%
“…However, we did find that changes in lncZEB1-AS1 expression were closely linked to changes in AKT activation and associated signaling in these cells. Through kinase activity assays and qRT-PCR, we ultimately found that lncZEB1-AS1 can enhance PI3K-AKT signaling in order to upregulate MMP2, MMP7, and MMP9 in HCC cells, thereby promoting tumor metastasis, consistent with prior reports highlighting the importance of AKT signaling in HCC onset and progression [35][36][37][38][39][40][41]. Our data further suggested that lncZEB1-AS1 promotes EGFR upregulation in HC cells, thereby enhanced EGF-but not HGF-mediated activation of PI3K-AKT signaling.…”
Section: Discussionsupporting
confidence: 88%
“…6c). Rescue experiments were performed with IGF-1 (a potent activator of PI3K/AKT signaling 18,23 ) in AML12. The IGF-1 treatment upregulated p-AKT S473 , and effectively restored the proliferation in TCTP-KD hepatocytes ( Supplementary Figs.…”
Section: Tctp Facilitates the Proliferation Of Hepatocytes By Activatmentioning
confidence: 99%